Styloid-shaped calcium oxalate crystals from piper species / Ibtisam Abdul Wahab, Hannis Fadzillah Mohsin and Zolkapli Eshak - Abdul Wahab, Ibtisam; Mohsin, Hannis Fadzillah; Eshak, Zolkapli (Universiti Teknologi MARA, Perlis, 2016)
This paper deals with the microscopic observation of the Piper species (Piperaceae family). This plant is also referred as pepper, which is widely used as a spice. From the literature search, the leaf and stem parts from a number of Piper were submitted to analyses under optical and scanning electron microscopy (SEM). Three crystalline categories, which consist of pure calcium, oxalate, mixtures of oxalates and sulfates, and combinations of oxalates, sulfates and silica; were viewed. These crystal rosettes and silicified crystals were described as unpublished reports. Therefore, a research is carried out in order to provide more biochemical understandings to the complex taxa of these plants. The alcoholic extract of the powdered fruits from both black and white peppers were investigated. It is aimed to record the morphological characteristics of the calcium crystals via SEM. From the photomicrographs, it was found that black pepper sample contained small intracellular crystals of calcium oxalate, particularly the styloids. Other documented Piper’s crystal formations such as the cuneiform or the wedge-shaped, tabular, cubic, prismatic, raphides and druses, are absent. Unfortunately, the crystal from white pepper sample was not observed. It is concluded that the shape and size of the calcium oxalate crystals in this plant could be used in the pharmacognostical evaluation of the Piper species.